This is me: A qualitative investigation of young people's experience of growing up with visual impairment. - Alexandra O Robertson (Public Library of Science (PLoS), 2021)
Background Childhood visual impairment (VI) has a profound impact on many aspects of childhood and adolescence. This is well-documented in cross-sectional and/or quantitative studies utilizing self-report instruments which compare children with and without VI. Young people's views on the experience of growing up with VI as a developmental, change-driven process remain largely unexplored. Methods As part of our broader research programme on quality of life of visually impaired children and young people in the United Kingdom, in-depth, semi-structured interviews were conducted between March and June 2015, with a stratified sample of 17 young people with VI, aged 16-19 years. An age-sensitive, empirically-based topic guide encouraged retrospective reflections on participants' experiences of growing up with VI, including age-normative and vision-specific challenges. Results Descriptions of growing up with VI largely centered on an overarching higher-order theme labelled becoming me. Four themes representing everyday activities, attitudes, preferences and perceptions in relation to i) social relationships, ii) independence and responsibilities, iii) the future, and iv) rising to challenges emerged and were used by participants in their description of three stages in which they developed a sense of self: i) laying the foundations, ii) testing the waters, and iii) this is me. Differences in manifestation of VI influenced how young people made sense of their experiences and their sense of self. Conclusions Findings are discussed in relation to normative and vision-specific changes in psychosocial development during adolescence, including the development of identity. They highlight the need for ongoing monitoring of subjective well-being in a clinical population with a unique early life course trajectory.